2011
DOI: 10.1111/j.1654-1103.2011.01353.x
|View full text |Cite
|
Sign up to set email alerts
|

Fairy rings caused by a killer fungus foster plant diversity in species‐rich grassland

Abstract: Questions: Does the fairy ring fungus Agaricus campestris affects spatial distribution of co-existing plant species? Is ring development related to changes of soil physical, chemical, enzymatic and microbiological properties? What are the causes of weakening and subsequent luxuriance of vegetation during fairy ring dynamics in the soil? Location: Species-rich, mowed calcareous grassland, central Italy (43° 17′26″ N, 12° 51′29″ E). Methods: Fairy rings were monitored for total plant biomass, species richness an… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

2
34
1

Year Published

2013
2013
2023
2023

Publication Types

Select...
9
1

Relationship

1
9

Authors

Journals

citations
Cited by 59 publications
(40 citation statements)
references
References 49 publications
2
34
1
Order By: Relevance
“…Within the zone of most intense fungal growth, the grass is often killed, and this effect has been attributed to a lack of moisture and to hydrocyanic acid produced by the fungus [ 45 , 46 ]. The occurrence of fairy rings in natural vegetation has simultaneous contrasting effects of both stimulation and a parasitisation of plant species in adjacent zones, producing concentric regular bands of lush and scorched vegetation [ 47 ]. In soils colonized by M .…”
Section: Discussionmentioning
confidence: 99%
“…Within the zone of most intense fungal growth, the grass is often killed, and this effect has been attributed to a lack of moisture and to hydrocyanic acid produced by the fungus [ 45 , 46 ]. The occurrence of fairy rings in natural vegetation has simultaneous contrasting effects of both stimulation and a parasitisation of plant species in adjacent zones, producing concentric regular bands of lush and scorched vegetation [ 47 ]. In soils colonized by M .…”
Section: Discussionmentioning
confidence: 99%
“…Values of the water drop penetration time > 1 h indicate that below-canopy soils are extremely hydrophobic [ 73 ]. It is well known that soil microbes, such as fairy-ring forming fungi [ 52 , 74 ], as well as the biochemical quality of soil organic matter [ 75 ] may contribute to produce soil water repellency. Previous studies reported that sandy texture, low pH and high organic C content are all factors that promote the development of soil water repellency [ 73 , 76 ].…”
Section: Discussionmentioning
confidence: 99%
“…Thus, the dispersal ecology of fairy ring fungi is not conducive to generating the linear biomass fronts needed to induce spiral formation under ‘normal’ conditions. We note, however, that despite the infrequent observation of spirals, incomplete fairy rings (fairy arcs), with free edges are commonly seen and widely reported [ 3 , 7 ]. It is unclear whether the widespread observation of free-edges that do not rotate poses a fundamental challenge to the predictions of the Davidson model, or whether observed arcs arose from processes that would not be expected to create spirals (e.g.…”
Section: Discussionmentioning
confidence: 84%